Super Chicken Nugget Boy and the Massive Meatloaf Man manhunt - Lewis, Josh (Disney/Hyperion Books, 2011)
Gordonville's "best of the breaded," Super Chicken Nugget Boy, faces his most dreaded adversary yet when Massive Meatloaf Man emerges from the woods.